Origin, Spread And Impact Of Islam On Nandi Traditional Religion And Culture: A Case Of Nandi County, Kenya - Murgor, Abraham Kiprotich; Rop, Bernard Kipsang (Machakos University Press, 2021)
In recent times, Islamic religion has been expanding rapidly at the global, regional and local levels. The presence of this religion in Nandi County and its evidence of growth raise the need to comprehend, with comparative ease, its origin, spread and impact on Nandi traditional religion and culture from 1850 to 2012, which has not lately been the subject of scholarly research. The main objective of this research-related work was to investigate the origin, impact and spread of Islam in Nandi County; apart from analyzing other factors that contributed to the acceptance and/or rejection of the religion by the Nandi people, which further enhanced its subsequent spread. Cross-cultural and Islamization theories were applied in collecting data and bridging the gap in knowledge by utilizing both qualitative design and survey data collection methods to arrive at conclusive findings. It was revealed that the spread of Islamic religion in Nandi County involved various factors such as socio-cultural, economic, religious and doctrinal, among others. Quality information was delineated on proselytism in a cross-cultural context and promotion of inter-faith dialogue which government policy-makers, other stakeholders, students, researchers and professionals should find both stimulating and useful. This data is vital in addressing the developmental agenda for Nandi County; particularly in areas related to recently launched competency-based curriculum education, historical and cultural heritage, as well as indigenous religion.
Keywords: Islam; Nandi; Traditional and cultural religion; Doctrinal proselytism; Competency-based education